(untitled) (Bangladesh Journal of Psychiatry, 2019)
The prevalence of psychiatric disorders is on rising trend in the country. This two stage nationwide multicentric community based cross sectional study was conducted by National Institute of Mental Health (NIMH), Dhaka during the period of September 2017 to July 2018 to determine the prevalence of psychiatric disordes and to identify common types of psychiatric disorders as well as to find out the physical illness in Bngladesh. In the first stage 19800 respondents in 140 clusters aged between 7 years and above were approached by the trained data collectors with standard printed questinnaires to collect information. Among them 19692 respondents were finally interviewed. Diagnoses of psychiatric disorders were made in the second stage of interview by research psychiatrists following DSM 5 diagnostic criteria of psychiatric disorders. The results showed that, the prevalence of psychiatric disorders was found 13.7% among population 18 years and above and 17.3% below 18 years of age. Division wise prevalence of adult psychiatric disorders were 15.5% in Rajshahi, 14.8% in Rangpur, 14.7% in Khulna, 14.2% in Dhaka, 13.8% in Chittagong, 13.6% in Sylhet and 13.0% in Barishal. Among total diagnosis of psychiatric disorders major depressive disorder were 24.8%, somatic symptom disorder 15.9%, generalized anxiety disorder 13.9%, neurodevelopmental disorders were 10.5%, schizophrenia spectrum and other psychotic disorders 4.7%, conduct disorder 4.7%, bipolar and related disorders 3.7%, obsessive compulsive disorder 3.1%, conversion disorder 1.8%, eneuresis 1.3% and dementia 1%. Data of this community survey will be used for planning of mental health services in Bangladesh. Bang J Psychiatry 2019; 33(1): 1-6